MEASURING THE RETAIL MIX ON PURCHASE DECISIONS DURING COVID-19 PANDEMIC - Johanes Babtista Barca Sally Kembaren; Herning Herning Indriastuti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The research of this study was to measure the influence of the retail mix on purchase decisions at the retail store Pramuka Mart Samarinda during the covid-19 pandemic. Samples were taken by accidental sampling as many as 111 respondents. The analytical technique used in this study is multiple linear regression analysis using the SPSS 23 program. The results of the study prove that product, price, promotion, and location have a positive and significant effect on purchasing decisions. While the service and store atmosphere have a positive but not significant effect on purchasing decisions